Opportunistic Manager and Capital Structure Decision of Property Companies in Indonesian Capital Market - Anastasia, Njo; Lorenza, Delyn (SBM ITB, 2019)
Abstract. An opportunist manager in property companies tend to take opportunity for himself while aggrieving the owner over the decision. This study focuses on determining the effect of managerial opportunism on capital structure decisions within property companies. Control from blockholders and capital market conditions plays a role in controlling opportunistic managers towards funding decisions. The data collected covers 25 property companies from 2000-2016 listed on Indonesia Stock Exchange. The analysis of data uses logistic regression that is able to measure capital structure decision on dummy variable. The conclusion shows that managerial opportunism and capital market condition influence the decision of capital structure, while outside blockholders on the other hand gives no effect. The contribution of the study indicates that the role of managers in company is deeply influential, that every manager who acts opportunistically would degrade the company's performance and harms the shareholders as well as investors.Keywords: agency conflict; capital structure decision; managerial opportunism; outside blockholders; stock market conditionAbstrak. Peran manajer pada perusahaan properti yang opportunis cenderung mengambil kesempatan untuk dirinya, sehingga pemilik perusahaan dirugikan. Penelitian ini bertujuan untuk mengetahui pengaruh managerial opportunism di perusahaan sektor properti terhadap keputusan struktur modal. Kontrol dari outside blockholders dan stock market condition akan berperan dalam mengendalikan manajer yang oportunis dalam pengambilan keputusan pendanaan. Pengambilan data dimulai dari tahun 2000-2016 dan diperoleh 25 perusahaan sektor properti yang terdaftar di Bursa Efek Indonesia. Analisa data menggunakan regresi logistic yang mampu mengukur keputusan struktur modal dengan dummy variabel. Hasil penelitian menunjukkan managerial opportunism dan stock market condition berpengaruh terhadap keputusan struktur modal, sedangkan outside blockholders tidak berpengaruh terhadap keputusan pendanaan. Implikasi dari penelitian ini menunjukkan bahwa peran manajer dalam perusahaan adalah penting, sehingga setiap manajer yang bertindak oportunis akan menurunkan kinerja perusahaan dan merugikan pemegang saham serta investor.Kata kunci: konflik keagenan; keputusan struktur modal; managerial opportunism; outside blockholders; stock market condition